Pola Komunikasi Antar Pribadi Presenter dan Reporter Siaran Live Program "Special Report" Di Inews TV - Irawan, Novida; Nurijadi, Bintang (Jurnal Mahardika Adiwidia, 2023)
Â Speaking and news processing skills are very important for a presenter and reporter, so that the delivery of messages to the public is conveyed properly. In this case, communication, especially interpersonal communication and coordination before the news is broadcast, becomes the main point so that there will be no mistakes or miscommunication when the presenter is broadcasting live with the reporter. The purpose of this research is to understand how to review the pattern of interpersonal communication between presenters and reporters through the concept of Jendela Johari (presenters and reporters of special report programs on INews TV). As for analyzing this research, it uses the Johari window concept which consists of four quadrants, namely, Open self, Blind Self, Hidden Self and Unknown Self. This study also uses a qualitative approach with descriptive research methods in order to describe the data results completely and clearly. Data were collected by participant observation and unstructured interviews. Data were analyzed by source triangulation method. The results of the research that have been found are that interpersonal communication that occurs between the presenter and the reporter is in accordance with the Johari window concept, namely open self, openness of giving information, blind self, a condition where there are obstacles or difficulties experienced but one party does not know it, hidden self where the condition is due to If there are obstacles or obstacles, communication before the broadcast does not occur which results in things that we do not know but are known to others. and Unknown Self where no one knows about the news. The communication process that occurred between the presenter and the operator before the live broadcast was through telephone media, and was held during breaking news which became an opportunity for the presenter to ask for more updated information, and so that questions from presenters and answers by reporters are connected